Effect of feeding systems on the egg production of Fayoumi Hens of Model Breeding units under PLDP Programme in Bangladesh - Hasnath, Md. Rasheed (2002)
One hundred and Sixty two, 36 weeks old Fayoumi were used in a study conducted to investigate the effects of feeding regimes on the performance of laying hens. They were randomly allotted into three farmers, who run the two different feeding regimes of ad libitum and restricted level of 80% of ad libitum feeding in same shed, same management and same environmental conditions. Average Live weight, egg weight and Feed conversion Ratio showed significant (P<0.05) difference between ad libitum and restricted feeding regimes. Egg production, Laying house mortality, Egg shape Index, Egg shell weight, Egg shell thickness and some selected egg quality characters (Albumen Index, Yolk Index and Haugh Unit) showed no significant (P>0.05) difference between the two feeding regimes. But Egg shell percentage showed significantly (P<0.01) difference between the two feeding regimes.In Hatching characters, the fertility and hatchability percentage showed significantly lower in restricted fed groups than ad libitum fed groups. But the quality of the Day Old Chicks showed no significant difference between the two feeding regimes respectively. Economically. It is viable to restrict the feeding of Fayoumi laying hens in intensive village conditions of Bangladesh since this will reduced the cost of production. However, the level of restriction should be moderated by the performance of the birds. It is concluded that Fayoumi laying hens can be restricted to 80% of ad libitum feeding without adverse effect on performance.